Were the unfinished nursing care occurrence, reasons, and consequences different between COVID-19 and non-COVID-19 patients? A systematic review - Stefania Chiappinotto; Aysun Bayram; Luca Grassetti; Alessandro Galazzi; Alvisa Palese (BMC, 2023)
Abstract Background Unfinished Nursing Care (UNC) has been documented also during the Coronavirus (COVID-19) pandemic; however, while several secondary studies were conducted before this period to summarise occurrences, reasons, and consequences of UNC and provide a global picture of the phenomenon, no synthesis of the evidence produced during the pandemic has been documented to date. Therefore, the aim of this review is to identify differences, if any, in the UNC occurrence, reasons, and consequences perceived by nurses caring for COVID-19 and non-COVID-19 patients. Methods This study is a systematic review (PROSPERO CRD42023410602). According to the Population, Exposure, Comparator, and Outcomes framework, primary comparative cross-sectional, longitudinal, and cohort studies, randomised/non-randomised controlled trials were included from Medline, CINAHL, and Scopus, collecting perceptions of nurses with tools measuring UNC between COVID-19 and non-COVID-19 patients and published in English, Italian, or Turkish. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline and Johanna Briggs Quality Appraisal Tool were used, and findings were summarised narratively. Results Five hospital-based cross-sectional studies using the self-administered MISSCARE and UNC Survey comparing data collected (a) before the pandemic vs. in the first wave; (b) before, in the second and in the third wave; and (c) simultaneously among COVID-19 and non-COVID-19 patients in the second wave. Three main patterns emerged suggesting a higher UNC occurrence among COVID-19 patients in the first wave, less occurrence among them compared to non-COVID-19 patients in the second wave, and contrasting findings with some in favour and others in contrast to COVID-19 patients. Similar patterns emerged regarding UNC reasons while no studies investigated the UNC consequences. Conclusions In the first wave, COVID-19 patients were likely to be at increased risk of UNC, while in later waves non-COVID-19 patients were at increased risk of UNC. Reasons also were different across waves. Findings documented during the COVID-19 pandemic may help to prevent UNC in future disasters.